METODE PELAKSANAAN DAN ESTIMASI BIAYA PELAKSANAAN PROYEK KONTRUKSI PEMBANGUNAN GEDUNG SATPOL PP KABUPATEN MAJALENGKA - Jahar Irawan (PROCEEDING STIMA)
Estimation, in the general sense, is an attempt to assess or estimate a value through calculation analysis and based on experience. Likewise, with the estimated cost in a construction project, it is certainly intended to estimate the value of financing a project.The construction cost analysis process is a process for estimating direct costs which are generally used as a basis for bidding. One method used to estimate construction costs is to calculate in detail the unit price of work based on index or coefficient values for analysis of material costs and worker wages. The construction project of the Satpol PP building in Majalengka Regency is located on Jl. Raya Tonjong - Pinangraja No. 50, in Cicenang Village, Cigasong District, Majalengka District, West Java. with a contract value of Rp. 2,454,894,000.00 within 150 calendar days